2006
DOI: 10.1093/occmed/kql034
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported work-related health problems from the Oslo Health Study

Abstract: A substantial proportion of common health problems in the Oslo population were attributed to working conditions. This implies a large preventive potential and call for increased preventive efforts targeted at known risk factors in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 35 publications
4
45
0
3
Order By: Relevance
“…The neck and shoulder pain prevalence estimates in our study were similar to estimates of 52% found among workers aged 15-66 years in Norway (31). The moderate/severe pain prevalence in our study was also similar to the 19% reporting to be intensely bothered by pain during the preceding four weeks in a cohort of mainly non-manual workers (12).…”
Section: Discussionsupporting
confidence: 89%
“…The neck and shoulder pain prevalence estimates in our study were similar to estimates of 52% found among workers aged 15-66 years in Norway (31). The moderate/severe pain prevalence in our study was also similar to the 19% reporting to be intensely bothered by pain during the preceding four weeks in a cohort of mainly non-manual workers (12).…”
Section: Discussionsupporting
confidence: 89%
“…Everyone in Oslo County born in 1970, 1960, 1955, 1940-1941, and 1924-1925 were invited by letter to attend a health screening, and the three youngest cohorts were selected for our present study (N=26 074). Of these people, 10 712 (41%) attended a physical examination or filled out at least one questionnaire in the Oslo health study (17). An age-specific supplementary questionnaire, which included questions on musculoskeletal pain, was returned by 8594 persons (33%).…”
Section: Study Populationmentioning
confidence: 99%
“…The response frequency was higher among the women than among the men, and it increased with age. Persons with little education, low income, disability benefit, or nonwestern origin were under-represented (17). We have studied the 7293 (28%) respondents to this questionnaire with data on musculoskeletal pain, occupation, and job characteristics, 4042 women and 3251 men (table 1).…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations